Modern Principles of Ensuring Blood Component Infection Safety - Saidov A.B; Kurbonova Z.Ch; Serdal Kokrmaz,; Sayfutdinova Z.A.; Shomansurova G.E (Zien Journals, 2023)
The main causative agents of parenteral infections are human immunodeficiency viruses, hepatitis B and C viruses. The impossibility of replacing blood with synthetic components and parenteral infections determines the relevance of increasing the safety of blood transfusion
Keywords: Donor; recipient; blood transfusion infections; hepatitis B